Validitas Buku Ajar Ekologi Berbasis Kearifan Lokal untuk Mengembangkan Sikap Ilmiah Mahasiswa - Hunaepi, Hunaepi; Firdaus, Laras; Kurnia, Nova (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2016)
This study aims to describe the validity of local wisdom-based ecology teaching books to develop students’ scientific attitudes. This research is a qualitative descriptive study to assess and obtain a valid ecological textbook in developing the students’ scientific attitudes. Ecology textbooks are validated by 4 (four) validators. The results of the study indicate that; 1) the validator’s assessment of textbooks developed from aspects of content validity and construct validity is categorized as valid with a range of scores Ëƒ 3.6 with reliability for each component having a percentage agreement of Ëƒ 75%. This shows that local wisdom-based ecology teaching books are valid and can be used in learning activities.